2020
DOI: 10.1002/ejoc.202000954
|View full text |Cite
|
Sign up to set email alerts
|

Selective Vicinal Diiodination of Polycyclic Aromatic Hydrocarbons

Abstract: Vicinally diiodinated polycyclic aromatic hydrocarbons (I2‐PAHs) are accessible from the corresponding diborylated B2‐PAHs through boron/iodine exchange. The B2‐PAHs have been prepared via twofold electrophilic borylation reactions templated by a vicinally disilylated benzene. Our protocol is applicable to fluorenes, acenes, annulated acenes, oligoaryls, and even [5]helicene. Using B2‐naphthalene as the example, we have shown that the reaction scope can, in principle, be expanded to include the synthesis of vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 96 publications
2
6
0
Order By: Relevance
“…While a dihedral angle of 30.4°was found for [5]helicene in the complex with the PBI cyclophane, this angle is, at 41.4°, significantly larger in the crystal structure of the free guest reported in literature. [46] Both values, as well as observed PBI core twists are in good agreement with those obtained from theoretical calculations (see below).…”
Section: Resultssupporting
confidence: 87%
“…While a dihedral angle of 30.4°was found for [5]helicene in the complex with the PBI cyclophane, this angle is, at 41.4°, significantly larger in the crystal structure of the free guest reported in literature. [46] Both values, as well as observed PBI core twists are in good agreement with those obtained from theoretical calculations (see below).…”
Section: Resultssupporting
confidence: 87%
“… 22 Comparison of the structure of 1-Br to that of the all carbon [5]helicene C is noteworthy. 23 In 1-Br the C9–C10–C11–C20 and C1–C10–C11–C12 torsion angles ( Fig. 5 ) are greater (34.6(5)° and 24.1(5)°, respectively) than the analogous angles in C (32.3(2)° and 20.2(2)°).…”
Section: Resultsmentioning
confidence: 89%
“…Of the molecules studied in this paper, crystal structures of naphthalene and [ n ]­helicenes with n = 3–7 and 9–11 have been synthesized with more than one polymorph obtained for [5]­helicene and [7]­helicene. , With the exception of [3]­helicene, X-ray crystal structures were deposited to the CSD, which we used to compare with the structures within our CSP landscapes. We found that the CSP landscapes (Figure ) were able to reproduce most of the experimentally known crystal structures.…”
Section: Results and Discussionmentioning
confidence: 99%